دراسة الهامش التسويقي والكفاءة التسويقية لزيت الزيتون المسوق في محافظة طرطوس (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
يهدف هذا البحث إلى دراسة الهامش التسويقي والكفاءة التسويقية لزيت الزيتون وتقديرهما للموسمين الزراعيين 2006-2007 موسم إنتاج ,2007-2008 موسم معاومة , من خلال دراسة أسعار البيع من المنتجين وتكاليف الوظائف التسويقية والإنتاجية  التي تؤدى على المنتَج ( زيت الزيتون) خلال المسلك التسويقي, حققت الهوامش التسويقية ( المطلق والنسبي ومعدل الزيادة السعرية) لحلقة المستهلكين المحليين المرتبة الأولى بين الحلقات المدروسة مسجلة ( 73.53 ل.س , 41.86 % , 71.99%) على الترتيب  في موسم الإنتاج, (65.6ل.س ,30.05% ,42.97 %) على الترتيب  في موسم المعاومة. وازدادت الكفاءة التسويقية  في موسم المعاومة عنه في موسم الإنتاج الجيد وفق المؤشر الأول لجميع أنواع الزيوت الممتاز والجيد وشبه الجيد مسجلة على الترتيب في موسم المعاومة ( 88.21, 84.06 , 85.68 ) %  ,و في موسم الإنتاج الجيد ( 87.82 , 78.09 , 77.59) %, أما وفق المؤشر الثاني فنلاحظ ارتفاع الكفاءة التسويقية في موسم الإنتاج الجيد مقارنة بموسم المعاومة  مسجلة ( 15.99, 8.64 , 3.29 ) % في موسم الإنتاج ,(7.6, 1.55, 0.83)% في موسم المعاومة للزيت الممتاز والجيد وشبه الجيد على الترتيب. The research aims to estimate olive oil marketing margin and marketing efficiency for two seasons, 2006- 2007  production season and 2007- 2008  alternate season, through the study of sales prices from producers and the costs of marketing and production functions of olive oil throughout the whole marketing process. Marketing margin and marketing efficiency are the most important indicators  of the marketing process success. The marketing margins (absolute, relative, and average increase) of the local consumers circle achieved the first order between the studied circles, recording  in order (73.53 s.p, 41.86 %, 71.99 % )  in the production season and (65.5 s.p, 30.05 %, 42.97 % )  in the alternate season. The marketing efficiency increased in the alternate season more than in the production season according to the first parameter to all oil kinds (extra virgin, virgin, and ordinary), recording in  the alternate season ( 87.82, 78.09, 77.95 )% in order. According to the second parameter, we noticed the increase of the marketing efficiency of all oil kinds (extra virgin, virgin, and ordinary) in the production season compared to the alternate season,  recording ( 15.99, 8.64, 3.29 )% in  the production season and (7.6, 1.55, 0.33 ) % in  the alternate season  for kinds (extra virgin, virgin, and ordinary) in order.